Lameness cases in cattle reported to the University Veterinary Hospital, Universiti Putra Malaysia from 2013 to 2017 - Ramanoon, Siti Zubaidah; Babatunde, Sadiq Mohammed; Abdul Razak, Noor Maisara; Mansor, Rozaihan; Syed Hussain, Sharifah Salmah; Shaik Mohamed Mossadeq, Wan Mastura (Veterinary Association Malaysia, 2018)
This study was designed to characterise the lameness cases in cattle reported to the University Veterinary Hospital (UVH) of Universiti Putra Malaysia (UPM), Serdang, Selangor. Medical records from 2013 to 2017 were reviewed and 136 cases of cattle diagnosed as lameness were retrieved. Information concerning signalment, location of lesions, and cause of lameness was analysed. Majority of the cases were reported in dairy (77%) compared with beef cattle (23%) with 73% being under semi-intensive management system. Foot lesions accounted for about 51% of cases, while lesions were more on the hindlimbs than the forelimbs (p<0.05). The most common diagnoses were trauma related causes and there was no significant difference (p>0.05) between foot lesions categorised either as infectious or non-infectious causes. A higher proportion (p<0.05) of the cases were weight-bearing rather than non-weight bearing lameness, thus suggesting mild to moderate lameness. The findings suggest that routine claw trimming may be necessary to improve weight-bearing balance as majority of the foot lesions were present on the hindlimbs. The findings depict that lameness remains a major health issue in dairy herds and information herein may assist practitioners in addressing such painful condition.